479. THE ROLE OF PET/CT IN PREDICTING THE PATHOLOGICAL RESPONSE TO NEOADJUVANT IMMUNOCHEMOTHERAPY FOR RESECTABLE ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (24th September 2022) - Yang, Weixiong; Wang, Xiaoyan; Luo, Hui; Zhang, Shuishen; Gan, Yi; Zeng, Bo; Liu, Zhenguo; Cheng, Chao
Abstract: Accurate assessment of residual disease of tumor and lymph nodes after neoadjuvant immunochemotherapy is crucial in the active surveillance for patients with ﻿pathological complete response (pCR) and the optimal extent of lymphadenectomy for patients with non-pCR. This post-hoc analysis aimed to evaluate the performance of 18F-FDG PET/CT to predict the pathological response to neoadjuvant immunochemotherapy for esophageal squamous cell carcinoma (ESCC). Fifty-eight resectable ESCC patients who received neoadjuvant PD-1 blockade in combination with chemotherapy were enrolled in the final analysis. The scans of 18F-FDG-PET/CT were acquired at baseline (scan-1) and after immunochemotherapy but prior to surgery (scan-2). Maximum standardized uptake value (SUVmax), mean standard uptake value (SUVmean), tumor-to-blood pool SUVmax ratio (SUVTBR), metabolic tumor volume (MTV) and total lesion glycolysis (TLG) were evaluated for their association with the pathological response to immunochemotherapy. The TLG and MTV at scan-1 was significantly lower in pCR than that in non-pCR group. At scan-2, the SUVmax, SUVmean, SUVTBR, TLG and MTV were significantly lower in pCR. Decrease in TLG and MTV between scan-2 and scan-1 were significantly higher in the pCR group. In the receiver operating characteristic curve analysis, SUVmax, SUVmean, SUVTBR, TLG and MTV in scan-2 showed excellent predictive value for the pCR of primary tumors. Furthermore, SUVmax at scan-2 were significantly higher in positive lymph nodes than that in negative ones, suggested a high negative predictive ability (98.6%) with a cut-off value at 1.4. The parameters of 18F-FDG PET/CT have the excellent performance for predicting pCR after the combined neoadjuvant immunochemotherapy in resectable ESCC.